Internet forensics - Jones, Robert, 1957 July 15- (O'Reilly, 2006)
Because it's so large and unregulated, the Internet is a fertile breeding ground for all kinds of scams and schemes. Usually it's your credit card number they're after, and they won't stop there. Not just mere annoyances, these scams are real crimes, with real victims. Now, thanks to Internet Forensics from O'Reilly, there's something you can do about it. This practical guide to defending against Internet fraud gives you the skills you need to uncover the origins of the spammers, con artists, and identity thieves that plague the Internet. Targeted primarily at the developer community, Internet Forensics shows you how to extract the information that lies hidden in every email message, web page, and web server on the Internet. It describes the lengths the bad guys will go to cover their tracks, and offers tricks that you can use to see through their disguises. You'll also gain an understanding for how the Internet functions, and how spammers use these protocols to their devious advantage. The book is organized around the core technologies of the Internet-email, web sites, servers, and browsers. Chapters describe how these are used and abused and show you how information hidden in each of them can be revealed. Short examples illustrate all the major techniques that are discussed. The ethical and legal issues that arise in the uncovering of Internet abuse are also addressed. Not surprisingly, the audience for Internet Forensics is boundless. For developers, it's a serious foray into the world of Internet security; for weekend surfers fed up with spam, it's an entertaining and fun guide that lets them play amateur detective from the safe confines of their home or office.